High-frequency supercapacitors based on carbonized melamine foam as energy storage devices for triboelectric nanogenerators. (January 2019) - Zhao, Man; Nie, Jinhui; Li, Hu; Xia, Mengyang; Liu, Mingyang; Zhang, Zailei; Liang, Xiaoqiang; Qi, Ruijie; Wang, Zhong Lin; Lu, Xianmao
Abstract: Triboelectric nanogenerators (TENG) are mechanical energy harvesting devices with pulsed output at frequencies ranging from a few to hundreds of hertz. Supercapacitors (SCs) are ideal energy storage devices for TENGs because of their high specific capacitance and excellent cycling performance, except that the poor high-frequency response of conventional supercapacitors limits their capability for storing pulsed energy at high frequencies. In this work, via a simple high-temperature carbonization process, we have fabricated carbonized melamine foams as electrode materials for high-frequency supercapacitors (HF-SCs). The resulting HF-SCs with a phase angle of − 80.1° and a specific areal capacitance of 132 μF cm −2 at 120 Hz were successfully employed as alternating current (ac) line filter for smoothing ripple current. When charged with a rotating TENG (R-TENG), the HF-SCs exhibited an energy utilization efficiency that is 20.3% higher than conventional activated carbon-based SCs, demonstrating the advantage of HF-SCs for storing pulsed energy generated by TENGs. Graphical abstract: fx1 Highlights: High-frequency supercapacitors (HF-SCs) were fabricated with melamine foams. A phase angle of − 80° at 120 Hz was achieved for filtering ripples of ac current. Charging by a rotating TENG with pulsed output at 1350 Hz was demonstrated. Efficiency of energy utilization was improved by 20.3% compared AC-SCs.